2023
DOI: 10.1101/2023.09.19.23295780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rare variation in noncoding regions with evolutionary signatures contributes to autism spectrum disorder risk

Taehwan Shin,
Janet H.T. Song,
Michael Kosicki
et al.

Abstract: Little is known about the role of noncoding regions in the etiology of autism spectrum disorder (ASD). We examined three classes of noncoding regions: Human Accelerated Regions (HARs), which show signatures of positive selection in humans; experimentally validated neural Vista Enhancers (VEs); and conserved regions predicted to act as neural enhancers (CNEs). Targeted and whole genome analysis of >16,600 samples and >4900 ASD probands revealed that likely recessive, rare, inherited variants in HARs, VEs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 158 publications
0
7
0
Order By: Relevance
“…Although we show that single cell chromatin accessibility is a strong predictor of cMN enhancer activity, even highly conserved and presumably functional enhancers can be surprisingly robust to mutagenesis 8,[112][113][114] . Therefore, to evaluate the functional consequences of our nominated CCDD variants, we selected 33 elements harboring cell type-aware candidate SNVs for in vivo humanized enhancer assays.…”
Section: Nominated Cell Type-specific Variants Alter Expression In Vivomentioning
confidence: 63%
See 1 more Smart Citation
“…Although we show that single cell chromatin accessibility is a strong predictor of cMN enhancer activity, even highly conserved and presumably functional enhancers can be surprisingly robust to mutagenesis 8,[112][113][114] . Therefore, to evaluate the functional consequences of our nominated CCDD variants, we selected 33 elements harboring cell type-aware candidate SNVs for in vivo humanized enhancer assays.…”
Section: Nominated Cell Type-specific Variants Alter Expression In Vivomentioning
confidence: 63%
“…We in part leveraged sequence conservation and constraint to prioritize pathogenic variants. However, while the known genes and cREs underlying cMN development are highly conserved, a conservation-based strategy may not identify pathogenic variants in human-specific and/or rapidly evolving sequences 114,120,121 . Strikingly, we also found that even relatively subtle differences in cellular composition and ATAC/RNA collection strategies can distort cognate gene estimates.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that brain size is relevant to HARE5 specific substitutions, but that HARE5 also impacts other features, related to the evolution of brain function. Further, the HARE5 locus also contains rare de novo mutations implicated in ASD 21,47,67 . We demonstrate that one ASD mutation, located adjacent to a human-specific variant, tempers enhancer activity in human NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…De novo copy-number variations (CNVs) and biallelic point mutations within HARs are associated with Autism Spectrum Disorder (ASD) 21,47 . Thus, we examined if there are any ASD-associated mutations in Hs-HARE5 nearby these variants using databases 21 .…”
Section: Increased Hare5 Enhancer Activity Relies On 4 Human-specific...mentioning
confidence: 99%
“…For example, a typical gain-of-function enhancer variant can result in ectopic gene expression and cause pathogenic effects in cells where the enhancer is normally inactive (Claussnitzer et al, 2015; Doan et al, 2016; Eufrásio et al, 2020; Kvon et al, 2020; Lewis et al, 2014; Putlyaeva et al, 2017; Turner et al, 2017; Yanchus et al, 2022). Likewise, loss-of-function enhancer variants often result in loss of enhancer activity in one cell type, while in other cell types, its activity is unaffected (Bengani et al, 2021; Bhatia et al, 2015, 2021; Shin et al, 2023; Spieler et al, 2014). These cell-type-specific effects of enhancer variants are difficult to capture with high-throughput methods such as massively-parallel reporter assays (MPRAs) and CRISPR inhibitor/activator screens, both of which are primarily performed in vitro (Findlay, 2021; Inoue & Ahituv, 2015; Maricque et al, 2018) or in one tissue (Brown et al, 2022; Capauto et al, 2023; Deng et al, 2023; Lagunas et al, 2023; Patwardhan et al, 2012; White et al, 2013).…”
Section: Introductionmentioning
confidence: 99%